HUBUNGAN ANTARA KONTROL GLIKEMIK DENGAN TINGKAT KUALITAS HIDUP PESERTA PROLANIS PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS PRAMBANAN SLEMAN - Putri, Eva Dwi Monicha; Ananda, RA Dewinta Sukma; Nurinda, Eva; Wulandari, Ari Susiana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
The Chronic Disease Management Program (Prolanis) is the key to controlling Diabetes Mellitus (DM) in Indonesia. The Special Region of Yogyakarta is one of the provinces of Indonesia that has the second highest prevalence of DM. The majority of DM patients are in Sleman Regency. This Prambanan Community Health Center (Puskesmas) is the second public health center with the highest prevalence of DM in Sleman. Quality of life (QOL) is the ultimate goal and important result of medical intervention for DM patients. The research methodology was a cross-sectional study conducted among 34 subjects who met inclusion and exclusion criteria. The results of this study showed that among the Prolanis participants with T2DM, 20 participants (58.8%) had controlled glycemic and 14 participants (41.2%) had uncontrolled glycemic. QOL was found to be higher among participants with controlled glycemic (80.0%) compared to participants with uncontrolled glycemic (28.6%), and the relationship was statistically significant (p<0.05). There was a relationship between glycemic control and quality of life.